2014
DOI: 10.1093/nar/gku942
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of subtelomeric VSG switching by Trypanosoma brucei TRF requires its TTAGGG repeat-binding activity

Abstract: Trypanosoma brucei causes human African trypanosomiasis and regularly switches its major surface antigen, VSG, in the bloodstream of its mammalian host to evade the host immune response. VSGs are expressed exclusively from subtelomeric loci, and we have previously shown that telomere proteins TbTIF2 and TbRAP1 play important roles in VSG switching and VSG silencing regulation, respectively. We now discover that the telomere duplex DNA-binding factor, TbTRF, also plays a critical role in VSG switching regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 75 publications
3
86
0
Order By: Relevance
“…These findings indicate that the telomeric NPT reporter is subject to the exclusion system operating in T. brucei. Analysis of Tb927.6.4430 supported previous reports of disrupted VSG silencing when telomere structure and/or function are compromised (26,34); knockdown of this novel telomeric TTAGGG repeat-associated factor (SI Appendix, Fig. S2 A and B) was associated with reporter and VSG derepression (SI Appendix, Fig.…”
Section: Significancesupporting
confidence: 80%
See 1 more Smart Citation
“…These findings indicate that the telomeric NPT reporter is subject to the exclusion system operating in T. brucei. Analysis of Tb927.6.4430 supported previous reports of disrupted VSG silencing when telomere structure and/or function are compromised (26,34); knockdown of this novel telomeric TTAGGG repeat-associated factor (SI Appendix, Fig. S2 A and B) was associated with reporter and VSG derepression (SI Appendix, Fig.…”
Section: Significancesupporting
confidence: 80%
“…2C and Movie S2) that is the site of the single active VSG-ES (10). Because all competent VSG-ESs are telomeric, we also used superresolution microscopy to assess VEX1 localization relative to the telomeric TTAGGG repeat-binding factor TRF2 (34). This revealed punctate nuclear TRF2 staining and VEX1 staining that was coincident with a TRF2 punctum (Fig.…”
Section: Significancementioning
confidence: 99%
“…Active transcription is known to favor homologous recombination (37). RNAi knockdown of the telomeric proteins TbTRF or TbTRF-interacting factor 2 (TbTIF2) increased VSG switching rates in T. brucei BF (38,39). The loss of these proteins appears to have enhanced repair and recombination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that telomere proteins are also important for maintaining subtelomere integrity and stability (24,25,27). In addition, telomeres suppress expression of nearby genes by telomeric silencing (28).…”
Section: Introductionmentioning
confidence: 99%